Optical Art. - Aust, Günter (Wuppertal : Kunst- und Museumsverein, 1969)
Albers, Josef ; Alviani, Getulio ; Anuszkiewicz, Richard ; Cruz-Diez, Carlos ; Duarte, Angel ; Fangor, Wojciech ; Gerstner, Karl ; Gonschior, Kuno ; Gredinger, Paul ; Ludwig, Wolfgang ; Luther, Adolf ; Mack, Heinz ; Mari, Enzo ; Mavignier, Almir ; Megert, Christian ; Morellet, François ; Parc, Julio Le ; Riley, Bridget ; Soto, Jesus Rafael ; Tomasello, Luigi ; Vasarely, Victor ; Wilding, Ludwig ; Yvaral, Jean-Pierre ; Zehringer, Walter
biog., tent. [11 p.]
Optical Art, Kunst- und Museumsverein, Wuppertal, 18.1. - 2.3.1969
Duits
kunstcatalogus